Non-linear relationship between the children’s dietary inflammatory index and asthma risk: identifying a critical inflection point in US children and adolescents - Junyu Xu; Meiping Zhu; Yi Shi; Qian Chen; Yan Zhu (Frontiers in Nutrition)
BackgroundAsthma, a chronic respiratory disease, is influenced by diet, which plays a key role in its onset and progression. The Children’s Dietary Inflammatory Index (C-DII) measures how diets impact inflammation in children and adolescents (6–19 years). The C-DII is a metric that quantifies the inflammatory potential of diet, with higher scores indicating more pro-inflammatory diets and a scoring range from −6.25 to 6.02. This study investigates the association between C-DII and asthma prevalence in US children and adolescents.MethodsData from the National Health and Nutrition Examination Survey (NHANES) 2013–2018 and 2021–2023 were utilized. Data from participants aged 6–19 years who completed dietary interviews and provided asthma-related information was included. The C-DII was calculated using 24-h dietary recall data, and data were categorized into quartiles. Asthma diagnosis was based on self-reported doctor diagnosis and current asthma status. Multivariable logistic regression, smooth curve fitting, threshold benefit analysis, and Restricted Cubic Spline (RCS) analyses were performed to evaluate the relationship between C-DII and asthma prevalence.ResultsData from 6,523 children and adolescents aged 6–19 years were analyzed. The median C-DII score was-0.026, and asthma prevalence was 18.63%. A U-shaped relationship was observed between C-DII and asthma prevalence, with the lowest risk at a C-DII score of-0.99. Subgroup analyses revealed variability in the association between C-DII and asthma across demographic groups. Age-based analysis indicated significant interaction (p = 0.047), with the weakest association observed in the 17–19 years age group. Ethnicity showed significant differences, particularly in Mexican-American (OR = 0.83, 95% CI: 0.70–0.97) and Non-Hispanic Black (OR = 1.56, 95% CI: 1.36–1.80) subgroups.ConclusionThis study underscores a significant non-linear association between C-DII and asthma prevalence in US children and adolescents, emphasizing the importance of balanced dietary patterns in mitigating asthma risk. Future longitudinal studies are warranted to confirm these findings and explore causal pathways.